“Laughing is very good”: the laughter and the puppet theater for childhood in Maria Mazzetti´s work – some parallels (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This paper aims to bring light to the ideas of humor and laughter found in one of the works of puppeteer Maria Mazzetti. By analyzing some of her texts, we seek to deliberate on topics such as the ideal perspective of entertainment for children, the conception of childhood which permeates her trajectory, and the relationship between laughter and what was understood about the New School movement. We start from the idea that Mazzetti’s conceptions can be expanded to other authors of the national puppet theater of the same period, which leads us to conclude that the reflections developed here suggest, in a certain way, aspects of the broader history of the Brazilian puppet theater.
Keywords: Maria Mazzetti; comic; laughter; childhood